Zarządzanie wiedzą w zespole wirtualnym jako istotny czynnik jego skutecznej pracy: Knowledge management in virtual team as an important factor of their effectiveness work - Mikuła, Bogusz; Stefaniuk, Tomasz (Management and Administration Journal, 2021)
The paper focuses on the problems of virtual teams, and knowledge managementin these teams. It presents the essential characteristics of virtual teams distinguish it from otherforms of group activities. It was described the essence of knowledge management systemin a virtual team as well as general recommendations of the process of its creation. It also indicated the importance of knowledge management on the effectiveness of the teams presentingresearch results among the ten functioning virtual teams.